The Mediating Role of Self-Efficacy in Shapins Financial Behavior - Munir, Sinthia Miftakul; Putri, Rizky Nur Ayuningtyas (Universitas Muhammadiyah Surakarta, 2024)
Purpose : This study explores the role of self-efficacy as a mediator in the relationship between financial literacy, lifestyle, locus of control, and pocket money in shaping students' financial behavior. Methodology : Employing a quantitative descriptive method, the research was conducted on 96 Muslim undergraduate students from Solo Raya, selected through purposive sampling. Data collection was carried out using a structured questionnaire, and analysis was performed with Structural Equation Modeling (SEM) using SmartPLS 4 software. Results : The results indicate that financial literacy, lifestyle, and locus of control have significant direct and indirect effects on financial behavior through self-efficacy. Additionally, pocket money serves as a significant factor influencing self-efficacy, which in turn impacts financial behavior. These findings highlight the crucial role of self-efficacy in fostering effective financial management among students. Applications/Originality/Value : The study offers valuable insights for designing financial education programs aimed at enhancing financial literacy, building self-efficacy, and responsibly encouraging financial practices. Such programs can prepare students for financial independence and long-term success.